2004
DOI: 10.1097/00006231-200404000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Simple techniques to reduce bowel activity in cardiac SPECT imaging

Abstract: The use of oral contrast and water improved the image variability and contrast by decreasing the infra-cardiac scatter. The improvement was even more significant in the oral contrast group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 4 publications
1
11
1
Order By: Relevance
“…Thus, the decrease in the MYO:EXC ratio in the delayed stress studies when the combined intervention was given may have been impacted by this natural biologic process. Overall, the MYO:EXC ratio was higher than the recommended target to non-target ratio of 2:1 and was also higher than results from previous studies [3,5,6,12,15,16,20,25]. It is suspected that the differences in imaging times between the studies played a role in the discrepancies of the ratio between studies.…”
Section: Discussioncontrasting
confidence: 58%
“…Thus, the decrease in the MYO:EXC ratio in the delayed stress studies when the combined intervention was given may have been impacted by this natural biologic process. Overall, the MYO:EXC ratio was higher than the recommended target to non-target ratio of 2:1 and was also higher than results from previous studies [3,5,6,12,15,16,20,25]. It is suspected that the differences in imaging times between the studies played a role in the discrepancies of the ratio between studies.…”
Section: Discussioncontrasting
confidence: 58%
“…Alternatively, several techniques have been studied to improve myocardial SPECT quality, including the intake of water [1], milk [2], iodinated oral contrast [3] or lemon juice [4], all of which reducing interfering abdominal activity, either by increasing the stomach volume or by accelerating the transit time of the tracer in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Interference from extracardiac radionuclide activity prevents the accurate interpretation of the true myocardial perfusion distribution (7,8). Compton scatter from the bowel degrades image quality in 99m Tc-sestamibi myocardial perfusion imaging, artifactually increasing count density in the inferior myocardial wall (9). In contrast, subdiaphragmatic activity is in the x-plane of the heart; the ramp filter artifact may decrease the count density of the inferior wall (10).…”
Section: Discussionmentioning
confidence: 99%
“…When SPECT is performed without attenuation correction, a glass of whole milk may suffice. Another study described the use of oral contrast and water to improve image variability and contrast by decreasing the infracardiac scatter (9). Another study demonstrated the advantages of a full stomach to reduce scatter artifact in the inferior wall, arising because of intestinal activity (15).…”
Section: Discussionmentioning
confidence: 99%